1978
DOI: 10.1126/science.200.4340.425
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes, Faults, and Nuclear Power Plants in Southern New York and Northern New Jersey

Abstract: Seismic activity in the greater New York City area is concentrated along several northeast-trending faults of which the Ramapo fault appears to be the most active. Three nuclear power plants at Indian Point, New York, are situated close to the Ramapo fault. For a reactor site in use for 40 years, the probability that the site will experience an intensity equal to or in excess of the design (safe shutdown) earthquake is estimated to be about 5 to 11 percent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

1980
1980
1996
1996

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 12 publications
0
22
2
Order By: Relevance
“…At least some faults formed by reactivation of older faults (Ratcliffe, 1971). Near New York City, Aggarwal and Sykes (1978) inferred that some such Mesozoic faults are seismically active, although Ratcliffe (1981a, b, c) questioned that inference.…”
Section: Atlantic Normal Faultsmentioning
confidence: 99%
“…At least some faults formed by reactivation of older faults (Ratcliffe, 1971). Near New York City, Aggarwal and Sykes (1978) inferred that some such Mesozoic faults are seismically active, although Ratcliffe (1981a, b, c) questioned that inference.…”
Section: Atlantic Normal Faultsmentioning
confidence: 99%
“…The seismicity resulting from this type of process would not be expected to be stationary. Some examples of well-known hypotheses that were invoked in the 1970s to explain NEUS earthquakes were the existence of a so-called Boston-Ottawa Seismic Zone (e.g., Diment et al, 1972;Sbar and Sykes, 1973), the hypothesis that NEUS earthquakes are associated with plutons (e.g., Simmons et al, 1976), and the hypothesis that seismic activity in this area is concentrated along NE trending faults, of which the Ramapo fault appeared to be the most active (Aggarwal and Sykes, 1978). We will address each of these in turn.…”
Section: Background: the Search For An Understanding Of Earthquake Prmentioning
confidence: 98%
“…The Ramapo fault is a Mesozoic border fault, which forms the northwestern margin of the Newark rift basin (NRB), and which was also active during pre-Mesozoic times (e.g., Ratcliffe, 1971;Ratcliffe, 1980). Aggarwal and Sykes (1978) studied locations, depths and focal mechanisms of earthquakes in the greater NYC area and concluded that seismic activity in this area is concentrated along northeast trending faults, of which the Ramapo fault appeared to be the most active. More recent studies of this area, however, produced results suggesting a more complicated relationship between earthquakes and geological features.…”
Section: The Ramapo Fault and The Dobbs Ferry Faultmentioning
confidence: 98%
“…An earlier microearthquake, located approximately 3 km north of the Verplanck sequence, was interpreted by Aggarwal and Sykes (1978) and Yang and Aggarwal (1981) to be the result of reverse faulting on a northeasterly striking branch of the Ramapo fault in response to a west-northwesterly directed maximum horizontal compressive stress. This event occurred on September 22, 1976, and is referred to as the Indian Point earthquake by Yang and Aggarwal (1981).…”
Section: Acknowledgmentsmentioning
confidence: 99%